Good Governance di Desa Adat Banjar: Transparansi Dana Krama Tamiu - Ngurah Kaler Widiartana; Nyoman Ari Surya Darmawan (Universitas Pendidikan Ganesha, 2020)
This research was conducted to reveal (1) Implementation of the principle of transparency in the management of krama tamiu funds in Banjar Adat Village, (2) The impact received by Tamiu Krama on the collection of Tamiu Krama Funds. Qualitative research methods with a descriptive approach. This study uses primary data and secondary data obtained through interviews, observations, and documentation which are further analyzed by reducing data, presenting data, analyzing data, and drawing conclusions. The results of the study are (1) the Banjar Adat Village in managing the krama tamiu funds is quite transparent because of the openness of the adat village management through paruman activities, (2) the management of the adat village in the management of the adat village government must make an oath or testify in the Pura Desa Adat Banjar to run a good and transparent government, (3) The impact of krama tamiu fund collection is to get protection, security, and assistance in the event of a calamity based on awig-awig, as well as the right to use traditional village facilities, and the close social impact between fellow village manners.